2019
DOI: 10.5614/j.eng.technol.sci.2019.51.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up of the Pyrolysis Process to Produce Silica from Rice Husk

Abstract: Rice husk is a potential alternative source of silica and silicon. The mechanism of heating (pyrolysis) for the decomposition of rice husk is an important factor in obtaining silica of high purity. Medium-scale pyrolysis to produce silica from rice husk serves as a bridge to connect laboratory-scale production to industrial-scale production. The purpose of this study was to model and scale up the pyrolysis process as a guidance for industrial-scale production. The research method used was experimentally based.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Based on previous research, the silica content in rice husk ash is 90-98% dry weight [4]. The second highest silica content is from bamboo leaf ash, which is 75.9% [5], while straw ash has a silica content of 75% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research, the silica content in rice husk ash is 90-98% dry weight [4]. The second highest silica content is from bamboo leaf ash, which is 75.9% [5], while straw ash has a silica content of 75% [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, utilizing SiO 2 in natural minerals is highly inefficient and might result in environmental problems when stored indefinitely (Abdurrahman et al, 2020). Therefore, SiO 2 from plant materials is in great demand for natural mineral Several studies related to the extraction of SiO 2 from biomass using rice husks (Sintha et al, 2017;Irzaman et al, 2020;Casnan et al, 2019), rice straw (Nazopatul et al, 2018;Hapsari et al, 2020), bamboo leaves (Irzaman et al, 2018;Aminullah et al, 2018), bagasse (Adli et al, 2018), and coir coconut (Anuar et al, 2020) have been reported. The sol-gel method extracted SiO 2 in those studies, followed by hydrolysis and subsequent condensation operations.…”
Section: Introductionmentioning
confidence: 99%
“…Rice husk ash contains approximately 80% to 90% SiO2 [3]. Casnan, et al (2019) reported that scaled-up production using pyrolysis could produce rice husk silica with 63.99% to 82.74% purity [4]. On the other hand, the sol-gel method using a technical grade solvent developed by Setyawan, et al (2019) yielded 62.83% of rice husk silica nanoparticles with 86.17% purity [5].…”
Section: Introductionmentioning
confidence: 99%